MOF derived porous Co@C hexagonal-shaped prisms with high catalytic performance. Issue 19 (9th September 2016) - Li, Hui; Chi, Le; Yang, Chao; Zhang, Liugen; Yue, Fan; Wang, Jide
Abstract: Abstract : There has been a continuous call for active, durable, and low-cost catalysts for a range of catalysis reactions. In this paper, porous Co@C composed of uniformly dispersed Co metal nanoparticles in hexagonal-shaped prisms carbon matrix were fabricated by in situ pyrolysis of hexagonal-shaped prismatic Co-MOF-74 crystals. The obtained nanoporous carbons have a high surface area of 195.2 m 2 /g and a strong magnetic response, thereby realizing fast molecular diffusion of reactant and easy magnetic separation. The resulting Co@C catalyst show a superior and durable catalytic activity for reduction of 4-nitrophenol (4-NP) to 4-aminophenol (4-AP). Moreover, Co@C can be recycled and still retains more than 75% of its original catalytic activity after 6 cycles. Therefore, it is reasonable to believe that such Co@C nanocomposites have great potential as a highly efficient and low-cost heterogeneous catalyst. It is believed that MOFs can be used to produce other catalysts with high porosity and uniformly dispersed active sites.